(untitled) (Journal of Statistical Research, 2024)
Change point detection aims to find abrupt changes in time series data. These changes denote substantial modifications to the process; these can be modeled as a change in the distribution (in location, scale, or trend). Traditional changepoint detection methods often rely on a cost function to assess if a change occurred in a series. Here, change point detection is investigated in a mixture-model-based clustering framework and a novel change point detection algorithm is developed using a finite mixture of regressions with concomitant variables. Through the introduction of a label correction mechanism, the unstructured clustering-based labels are treated as ordered and distinct segment labels. This approach can detect change points in both univariate and multivariate time series, and different kinds of change can be captured using a parsimonious family of models. Performance is illustrated on both simulated and real data. Journal of Statistical Research 2024, Vol. 58, No. 1, pp. 197-219.